Identifying indicators that can play a meaningful role in promoting creativity in SMEs: A South African study - G. J.P. Maas; T. J. De Coning; E. V.D.M. Smit (South African Journal of Business Management, 1999)
This study focused on identifying indicators that can play a meaningful role in promoting creativity in South African small and medium-sized enterprises (SMEs). Seven indicators of creativity for SME owners and four for the SME organisation were identified. The present profile of South African SME owners does not correspond with these indicators providing some clues to the lack of creativity in the SME sector.
Keywords: 650